Constituents of Volatile Oil from Bark of Clerodendrum serratum (L.) and its Antibacterial Activity. Issue 1 (2nd January 2018) - Noreen, Rahat; Intisar, Azeem; Ghaffar, Abdul; Jabeen, Farkhanda; Abid, Muhammad Amin; Din, Muhammad Imran; Irfan, Muhammad; Faiz, Faiza; Sattar, Tayyaba
Abstract: Volatile oil composition of the bark of Clerodendrum serratum (L.) was reported. Oil was extracted by hydrodistillation and analyzed through GC-MS. 48 Constituents were successfully identified that accounted for 93.35 % of the total composition. The most abundant constituents found in the bark were linoleic acid (20.1 %), α-zingiberene (10.3 %) o-cymene (9.3 %), palmitic acid, (9.0 %), oleic acid (7.0 %), and β-sesquiphellandrene (5.3 %). Moreover, antibacterial activity of oil was evaluated against four different pathogenic strains namely Methicillin-resistant Staphylococcus aureus (MRSA), Escherichia coli ( E. coli ), Methicillin-sensitive Staphylococcus aureus (MSSA) and Proteus spp. The results of antibacterial activity demonstrated that the activity of oil follows the principle of dose-dependency. The zone of inhibition at the maximum dose of 200 μL were 38 mm for Proteus spp., 34 mm for E. coli, 31 mm for MRSA and 30 mm for MSSA.